Faktor predisposisi dan dukungan suami dalam praktik pemberian makanan pendamping ASI (MP-ASI) pada bayi usia 6-12 bulan - Lailiyah, Eka Nur; Ningtyias, Farida Wahyu; Ratnawati, Leersia Yusi (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2025)
Predisposing factors and husband’s support in the practice of feeding weaning food infants aged 6-12 monthsBackground: Nutritional problems are caused by several factors, one of which is weaning food feeding. Objective: This research aims to analyze the predisposing factors and the husband's support for feeding weaning food to infants aged 6-12 months. Methods: This observational analytic study, using a cross-sectional approach, was conducted in the working area of Kemuningsari Kidul Public Health Center in Jember Regency. Eighty mothers of infants aged 6-12 months were chosen as the sample, and the sample selection was done using a simple random sampling technique. Meanwhile, the Chi-Square test and multiple logistic regression were used for the statistical analysis. Results: The research showed that most respondents were 26-35 years old, and their latest education was junior high school/equivalent. They were unemployed, had good knowledge, a positive attitude, family support, and no cultural influence. Fifty-four people (67,5%) had appropriate behavior in feeding weaning food, while the other 26 people (32.5%) had not. Besides, based on the results of the bivariate analysis, there was a relationship between occupation (p=0.007), knowledge (p=0.023), attitude (p=0.004), culture (p=0.000), and husband's support (p=0.008) with the practice of feeding weaning food. The results of the multivariate analysis indicated that culture was the dominant factor in feeding weaning food. Conclusions: Factors related to feeding weaning food to infants aged 6-12 months include work, knowledge, attitudes, culture, and husband's support. Culture is the most dominant factor.